Neuroepithelial bodies and terminal bronchioles are niches for distinctive club cells that repair the airways following acute notch inhibition - Sai Manoz Lingamallu; Aditya Deshpande; Neenu Joy; Kirthana Ganeshan; Neelanjana Ray; Rajesh Kumar Ladher; Makoto Mark Taketo; Daniel Lafkas; Arjun Guha (Cell Reports, 2024)
Summary: Lower airway club cells (CCs) serve the dual roles of a secretory cell and a stem cell. Here, we probe how the CC fate is regulated. We find that, in response to acute perturbation of Notch signaling, CCs adopt distinct fates. Although the vast majority transdifferentiate into multiciliated cells, a “variant” subpopulation (v-CCs), juxtaposed to neuroepithelial bodies (NEBs; 5%–10%) and located at bronchioalveolar duct junctions (>80%), does not. Instead, v-CCs transition into lineage-ambiguous states but can revert to a CC fate upon restoration of Notch signaling and repopulate the airways with CCs and multiciliated cells. The v-CC response to Notch inhibition is dependent on localized activation of β-catenin in v-CCs. We propose that the CC fate is stabilized by canonical Notch signaling, that airways are susceptible to perturbations to this pathway, and that NEBs/terminal bronchioles comprise niches that modulate CC plasticity via β-catenin activation to facilitate airway repair post Notch inhibition.